Ambivalent Journey : U.S. Migration and Economic Mobility in North-Central Mexico - Jones, Richard C., 1942- (Book collections on Project MUSE., 1995)
"Compares impact of US migration on municipios in the states of Coahuila and Zacatecas. Findings suggest there are important differences in the socioeconomic characteristics of migrants of the two areas and that the remittance of funds by migrants impacted the receiving communities in different ways. Concludes with an interesting speculation on possible impacts of free trade initiatives for rural municipios"--Handbook of Latin American Studies, v. 57.